Analisis Pembiayaan Akad Ijarah Multijasa Perspektif Ekonomi Islam - Arifin, Ria; Sultoni, Hasan (Universitas Muhammadiyah Ponorogo, 2024)
In the face of increasingly fierce competition, it requires Islamic financial institutions to manage funds effectively and efficiently, both for funds collected from the public and from owners or founders. One of the service products issued by BTM Surya Madinah is multijasa financing In carrying out each of its activities, LKS must follow sharia principles. In the principles of Muamalat Law, it is stated that all forms of muamalat are permissible except those prohibited by sharia. As is the case with the use of contracts. Every product issued by LKS must use the right contract. In the use of ijarah contracts in the application of multiservice financing products, there are visible oddities or oddities, there are differences between fatwa and muamalat fiqh. The agreement used seems to be just a fabrication to benefit Islamic financial institutions that carry out the financing.